Investigation of Concrete Base-Roadbed Surface Contact Variation-Induced Vibration Characteristics of Vehicle-Slab Track-Subgrade System considering Fluid-Solid Interaction - Kai-Wen Liu; Fei Yue; Qian Su; Bao Liu; Pengfei Zhou (Shock and Vibration)
The excessive pumping of fines in saturated roadbed surface layer, which is induced by the fluid-solid interaction under dynamic loads from high-speed train, is a special form of high-speed railway subgrade defect reported recently. This can deteriorate the interface between nonballasted track structure bottom layer and roadbed surface layer and therefore lead to associated contact variation with the moving of trains. According to the dynamic Biot’s equations known as u-p formulation and the vehicle-track coupling dynamics theory, a vertical vehicle-slab track-subgrade coupling vibration model is developed to investigate the aforementioned contact variation-induced dynamic behavior of the whole system considering the fluid-solid interaction. Dynamic measurements from a field case study are adopted to verify the computation model proposed. Based on the numerical model validated, the effects of three contact variation statuses (continuous contact, vibrating contact, and contact loss) on dynamic responses of track subsystem and subgrade subsystem, such as dynamic pore-water pressure, vertical accelerations, and dynamic displacements both in time and frequency domains, are investigated. Also, a sensitivity analysis involving rail speeds and lengths of contact loss zone is performed, and the critical length of contact loss zone is suggested.